Development of E-LKPD Based Website Lumio by Smart Material on the Potential of Indonesian Natural Resources in Geography Learning for Senior High School Students - Syafitri, Anggi Wahyu; Astutik, Sri; Nurdin, Elan Artono; Mujib, Muhammad Asyroful; Pangastuti, Era Iswara (CV Bumi Spasial, 2025)
Despite rapid technological advancements, traditional LKPD-based learning media, primarily paper or book-based E-LKPD, have not adapted to the evolving needs of modern education. This study followed the ADDIE model Analyze, Design, Development, Implementation, and Evaluation to develop E-LKPD materials on the potential of Indonesia's natural resources using the Lumio by Smart website. The product received very high validation scores from experts, with media and material expert validations both averaging 4.91 (Very Valid), and learning practitioner validation averaging 4.72 (Very Valid). Student feedback was also highly positive, with small and large groups scoring 4.52 and 4.72, respectively, in the 'strongly agree' range. Post-test results indicated that the E-LKPD significantly improved learning outcomes, with small and large groups achieving average scores of 84.4 (Good) and 88 (Very Good), both meeting the KKM standards. In conclusion, the Lumio by Smart-based E-LKPD is an effective tool for enhancing geography learning and has potential for wider application in educational contexts.